THE PROBLEM OF HISTORY OF PROGRESS OF TEST CULTURE IN UKRAINE - Shuliak, C.O. (Journal of Information Technologies in Education (ITE), 2010)
The article is devoted to the origin of test methods and their extension at the domestic space. It is determined that Ukraine is experiencing a new stage of development testology and test culture.